HDL-S1P: cardiovascular functions, disease-associated alterations, and therapeutic applications - Levkau, Bodo (Frontiers in Pharmacology, 2015)
Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid contained in High-density lipoproteins (HDL) and has drawn considerable attention in the lipoprotein field as numerous studies have demonstrated its contribution to several functions inherent to HDL. Some of them are partly and some entirely due to the S1P contained in HDL (HDL-S1P). Despite the presence of over 1000 different lipids in HDL, S1P stands out as it possesses its own cell surface receptors through which it exercises key physiological functions. Most of the S1P in human plasma is associated with HDL, and the amount of HDL-S1P influences the quality and quantity of HDL-dependent functions. The main binding partner of S1P in HDL is apolipoprotein M but others may also exist particularly under conditions of acute S1P elevations. HDL not only exercise functions through their S1P content but have also an impact on genuine S1P signaling by influencing S1P bioactivity and receptor presentation. HDL-S1P content is altered in human diseases such as atherosclerosis, coronary artery disease, myocardial infarction, renal insufficiency and diabetes mellitus. Low HDL-S1P has also been linked to impaired HDL functions associated with these disorders. Although the pathophysiological and molecular reasons for such disease-associated shifts in HDL-S1P are little understood, there have been successful approaches to circumvent their adverse implications by pharmacologically increasing HDL-S1P as means to improve HDL function. This mini-review will cover the current understanding of the contribution of HDL-S1P to physiological HDL function, its alteration in disease and ways for its restoration to correct HDL dysfunction.